Bacterial small RNAs in the Genus Rickettsia. (December 2015) - Schroeder, Casey; Narra, Hema; Rojas, Mark; Sahni, Abha; Patel, Jignesh; Khanipov, Kamil; Wood, Thomas; Fofanov, Yuriy; Sahni, Sanjeev
Abstract Background Rickettsia species are obligate intracellular Gram-negative pathogenic bacteria and the etiologic agents of diseases such as Rocky Mountain spotted fever (RMSF), Mediterranean spotted fever, epidemic typhus, and murine typhus. Genome sequencing revealed thatR. prowazekii has ~25 % non-coding DNA, the majority of which is thought to be either "junk DNA" or pseudogenes resulting from genomic reduction. These characteristics also define otherRickettsia genomes. Bacterial small RNAs, whose biogenesis is predominantly attributed to either the intergenic regions (trans-acting) or to the antisense strand of an open reading frame (cis-acting), are now appreciated to be among the most important post-transcriptional regulators of bacterial virulence and growth. We hypothesize that intergenic regions in rickettsial species encode for small, non-coding RNAs (sRNAs) involved in the regulation of its transcriptome, leading to altered virulence and adaptation depending on the host niche. Results We employed a combination of bioinformatics and in vitro approaches to explore the presence of sRNAs in a number of species within GenusRickettsia . Using the sRNA Identification Protocol using High-throughput Technology (SIPHT) web interface, we predicted over 1, 700 small RNAs present in the intergenic regions of 16 different strains representing 13 rickettsial species. We further characterized novel sRNAs from typhus (R. prowazekii andR. typhi ) and spotted fever (R. rickettsii andR. conorii ) groups for their promoters and Rho-independent terminators using Bacterial Promoter Prediction Program (BPROM) and TransTermHP prediction algorithms, respectively. Strong σ70 promoters were predicted upstream of all novel small RNAs, indicating the potential for transcriptional activity. Next, we infected human microvascular endothelial cells (HMECs) withR. prowazekii for 3 h and 24 h and performed Next Generation Sequencing to experimentally validate the expression of 26 sRNA candidates predicted inR. prowazekii . Reverse transcriptase PCR was also used to further verify the expression of six putative novel sRNA candidates inR. prowazekii . Conclusions Our results yield clear evidence for the expression of novelR. prowazekii sRNA candidates during infection of HMECs. This is the first description of novel small RNAs for a highly pathogenic species ofRickettsia, which should lead to new insights into rickettsial virulence and adaptation mechanisms.